A DFT based insights for molecular designing of pyridine dipyrrolide core with benzodithiophene-based acceptors for organic solar cells - Mashal Khan; Ayesha Tariq; Iram Irshad; Muhammad Adnan Asghar; Tansir Ahamad; Ke Chen (Scientific Reports)
Abstract This study introduces a new series of organic compounds (PPH1–PPH8) derived from a pyridine dipyrrolide (PDP) core, aimed at enhancing the efficacy of organic solar cells. Their light absorption and charge transport capabilities were improved by altering the terminal groups of a reference molecule (PPHR) with strong electron-withdrawing units. The density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were employed at the M06/6-311G(d, p) level to examine the electronic and photovoltaic features of the designed chromophores. The findings indicated a notable redshift in the absorption spectra, broadening the absorption range from 562.874 to 617.913 nm accompanied by a substantial decrease in the energy gap from 2.677 to 2.468 eV in PPH1–PPH8. These results indicated enhanced solar light absorption due to end-capped modification. Moreover, these compounds demonstrated lower exciton binding energies (0.460–0.509 eV), signifying effective charge separation and improved exciton dissociation. Calculations of open-circuit voltage (V oc), utilizing the standard acceptor (PC 71 BM), further validated their photovoltaic potential. Electron-hole analysis identified PPH5 as a highly promising candidate, demonstrating significant spatial separation of charge carriers. Therefore, this research study presents a novel class of PDP-based chromophores with tailored optoelectronic characteristics, providing significant insights for the advancement of next-generation organic photovoltaic materials.